Design, fabrication & experimental study of a mini solar cooling refrigerator for mechanical application - Hon, K.K (University Malaysia Sarawak, UNIMAS., 2005)
Solar Cooling Refrigerator is a device that can be used to produce cooling effect without utilization of electricity. It produce no noise or pollution. The main aim for this project is to design and fabricate solar absorption cooling refrigerator from scratch for producing small amount of cooling effect in cooling compartment.